Lightweight polyethylene‐hollow glass microspheres composites for rotational molding technology. Issue 5 (15th August 2020) - Stagnaro, Paola; Utzeri, Roberto; Vignali, Adriano; Falcone, Giulio; Iannace, Salvatore; Bertini, Fabio
Abstract: Innovative composites based on polyethylene (PE) filled with hollow glass microspheres (HGMs) were formulated and successfully prepared as suitable plastic materials for rotational molding technology. The HGMs here used allow to attain lightweight materials with a reduced resin content and appealing aesthetical qualities. To enhance filler dispersion and phase adhesion, thus improving the ultimate properties of the composite materials, two compatibilization strategies were adopted: namely, surface modification of HGMs by dodecyl(triethoxy)silane or addition during mixing of a maleinized PE as in‐situ coupling agent. The effectiveness of the surface treatments on HGMs was assessed by attenuated total reflectance Fourier‐transform infrared spectroscopy and thermogravimetric analysis investigations. PE‐based composites at various HGMs contents (5, 10, and 20 wt%) were prepared by melt blending. Morphology of untreated and modified HGMs, their dispersion in the composites as well as filler/matrix adhesion were investigated by SEM microscopy. Thermal, rheological and mechanical properties of the composites were studied in comparison with neat PE. Rotational molding tests carried out both in laboratory and industrial site demonstrated the feasibility of producing lightweight plastic items (weight reduction up to 17%) of excellent aesthetics on a large scale. Abstract :